Использование онтологии предметной области для снятия омонимии в естественно-языковых текстах - Лесько, О.Н.; Рогушина, Ю.В. (Проблеми програмування, 2017)
Разработан метод снятия различных видов омонимии в естественно-языковых текстах деловых, научных и правовых документов. Специфика метода заключается в том, что он не требует использования большого количества синтаксических правил и корпуса размеченных текстов, что значительно упрощает его реализацию и сокращает время, необходимое для создания и разметки корпуса текстов. Этот результат достигается как за счет использования онтологии предметной области, так и за счет особенностей синтаксических структур деловых, научных и правовых документов. Розроблено метод зняття різних видів омонімії у природномовних текстах ділових, наукових і правових документів. Специфіка методу полягає у тому, що він не вимагає використання великої кількості синтаксичних правил і корпусу розмічених текстів, що значно спрощує його реалізацію і скорочує час, необхідний для створення і розмітки корпуса текстів. Цей результат досягається як внаслідок використання онтології предметної області, так і за рахунок особливостей синтаксичних структур ділових, наукових і правових документів. The article analyses the clarification of various types of homonymy that can be executed without use of semantic information, but only on the basis of syntactic rules. This analysis shows how features of the syntactic structures of legislative and academic texts allow to reduce the number of formal rules required for parsing. A minimal set of syntactic rules necessary for the automatic analysis of such texts is proposed. A method of homonymy clarification in natural language business, scientific and legal text documents is developed. Proposed method does not require the use of a large number of syntactic rules and marked-up texts. Such specificity greatly simplifies the implementation and reduces the time required for creation and markup of text corpora. This result is achieved by use of domain ontology, and by the specifics of syntactic structures of business, scientific and legal documents. In addition, we demonstrate how the use of domain ontology allows to simplify the analysis of the test documents. As opposed to other systems of automatic processing of natural language texts that use domain ontology for semantic analysis too the domain ontology is used to highlight terms in the text and further morphological information of each word in wordy terms.